How the word of mouth marketing strategy influence the consumer buying interest? (A case of genestick product) - Wenas, Pearl Loesye; Natos, Christoffer Daniel; Rompas, Margresye Diana; Towoliu, Benny Irwan (Journal of Commerce, Management, and Tourism Studies, 2024)
The genestick product is a stick-shaped snack product made from onions in the Manado local language called kue kering biji-biji. This cake is produced by students from Politeknik Negeri Manado who are managed in groups in the form of micro-entrepreneurship, since it was sold it has stagnated, because it only uses a promotion strategy using a social media platform. Since the marketing strategy changed through word of mouth marketing, sales have increased. The purpose of this study was to analyze the effect of word of mouth marketing strategies on consumer buying interest in ginestick products. The research method used is quantitative descriptive, with data collection techniques through surveys, of 50 respondents. The analytical tools used are validity and reliability tests, correlation tests, regression tests, determination tests and hypothesis testing through the T test and F test. From some of these tests it is found that consumer buying interest is influenced by word of mouth marketing strategies. At the significance level of the hypothesis test (T and F tests) (0.001) and < the research error rate of 0.05 and with a coefficient of determination of 61.6%, it has a positive effect, which means that the higher the Word of mouth marketing, the higher the buying interest of Genestick product consumers.